2015
DOI: 10.1371/journal.pone.0140247
|View full text |Cite
|
Sign up to set email alerts
|

The Seasonal Dynamics of Artificial Nest Predation Rates along Edges in a Mosaic Managed Reedbed

Abstract: Boundaries between different habitats can be responsible for changes in species interactions, including modified rates of encounter between predators and prey. Such ‘edge effects’ have been reported in nesting birds, where nest predation rates can be increased at habitat edges. The literature concerning edge effects on nest predation rates reveals a wide variation in results, even within single habitats, suggesting edge effects are not fixed, but dynamic throughout space and time. This study demonstrates the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…While we predicted that nest predation by mammalian predators would increase with the density of habitat edges, we detected a positive relationship for all predator species. The influence of habitat edges on nest predation often varies with the predator community (Lahti 2001) and can be a dynamic process through time (Malzer and Helm 2015). Studies of this effect, however, have largely focused on agricultural landscapes with hard edges (Lahti 2001, Batary and Baldi 2004, Stephens et al 2004), while studies from lower‐contrast edges, such as the transition from marsh to playa, are less common (Suvorov et al 2014, Malzer and Helm 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we predicted that nest predation by mammalian predators would increase with the density of habitat edges, we detected a positive relationship for all predator species. The influence of habitat edges on nest predation often varies with the predator community (Lahti 2001) and can be a dynamic process through time (Malzer and Helm 2015). Studies of this effect, however, have largely focused on agricultural landscapes with hard edges (Lahti 2001, Batary and Baldi 2004, Stephens et al 2004), while studies from lower‐contrast edges, such as the transition from marsh to playa, are less common (Suvorov et al 2014, Malzer and Helm 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of habitat edges on nest predation often varies with the predator community (Lahti 2001) and can be a dynamic process through time (Malzer and Helm 2015). Studies of this effect, however, have largely focused on agricultural landscapes with hard edges (Lahti 2001, Batary and Baldi 2004, Stephens et al 2004), while studies from lower‐contrast edges, such as the transition from marsh to playa, are less common (Suvorov et al 2014, Malzer and Helm 2015). In our study, the influence of edge density on coyote nest predation had the highest posterior probability at 5000 m, which could indicate that the actual scale of this effect is larger than what we measured (Jackson and Fahrig 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in Scotland have shown significant seasonality in nest predation rates around spring. Nest predation rates were shown to peak in late April, and then slowly decline until late June (Malzer & Helm, 2015). If this seasonal predation effect is also seen in England, it may help account for the unusually high levels of predation seen in this experiment.…”
Section: Abiotic Edge Factors Affecting Predationmentioning
confidence: 53%
“…If this seasonal predation effect is also seen in England, it may help account for the unusually high levels of predation seen in this experiment. However it should be noted that although Malzer & Helm (2015) found an overall effect of season on nest predation, it did not influence the edge effect, which was constant year round.…”
Section: Abiotic Edge Factors Affecting Predationmentioning
confidence: 65%
See 1 more Smart Citation